(3GdWQb GdMcejIs - (3eMeO Hf CHj HcQ Hf CjhH Hf SYO GdRQYj GdOeTbj, CHh YHO Gddg, TeS GdOjf,J (B751 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QGaY OQLGJ ef TGA HGdYde hGdEjeGf aUd hSCdJ Yf GdMGce Ch GdhGdi Ydje HGdaQGSI hGdbQGFf s
(3BNQgG (B:s
(3hdgPG bGd gi CTHg hHGdLedI aef JCed ajeG PcQfG ai GdbQYI JHjf dg Cf Gdbhd HgG Chdi ef EjbGa GdeGd CHOkG MJi jUWdM GdeOYhf hHGddg GdJhajb hgPG BNQ cJGH GdWQb GdMcejI dGHf bje GdLhRjI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B106s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1111s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs